2018
DOI: 10.1111/lcrp.12137
|View full text |Cite
|
Sign up to set email alerts
|

Immediate interviewing increases children's suggestibility in the short term, but not in the long term

Abstract: Purpose Children sometimes receive misinformation after being formally interviewed about their experiences in cases of suspected abuse. Following decades of research, many guidelines have been produced for interviewers so they can obtain reliable statements in children, like, for example, the NICHD protocol. One might expect that completing an early interview following research‐based guidelines might guard against the incorporation of misinformation encountered later. The goal of the current experiments was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
(97 reference statements)
0
20
1
Order By: Relevance
“…So far, there exists only one study in which the impact of using a science-based interview protocol on the reporting of misinformation in children was examined using a similar procedure as has been employed in previous retrieval-enhanced suggestibility studies in adults (Otgaar et al 2019). In this study, we used the National Institute for Child Health and Development Protocol (NICHD Protocol;Lamb et al 2007), which is a developmentally sensitive interview method based on research on the development of children and how children talk about traumatic experiences (Lamb et al 2007;La Rooy et al 2015).…”
Section: Interviewing and Misinformationmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, there exists only one study in which the impact of using a science-based interview protocol on the reporting of misinformation in children was examined using a similar procedure as has been employed in previous retrieval-enhanced suggestibility studies in adults (Otgaar et al 2019). In this study, we used the National Institute for Child Health and Development Protocol (NICHD Protocol;Lamb et al 2007), which is a developmentally sensitive interview method based on research on the development of children and how children talk about traumatic experiences (Lamb et al 2007;La Rooy et al 2015).…”
Section: Interviewing and Misinformationmentioning
confidence: 99%
“…In our study on the impact of the NICHD Protocol on the reporting of misinformation (Otgaar et al 2019), 108 5-to 10year old children first viewed a video, after which half of the children were interviewed about this video using the NICHD Protocol while the other half was not interviewed. Then, all children received misinformation and final memory tests were conducted immediately following the misinformation (Experiment 1) or after 1 week (Experiment 2).…”
Section: Interviewing and Misinformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The NICHD protocol is an evidence-based protocol for interviewing alleged CSA victims (Benia et al 2015). The NICHD Protocol has been shown to elicit detailed (Cyr and Lamb 2009;Lamb et al 2003) and accurate (Otgaar et al 2018a(Otgaar et al , 2018b information from children. The NICHD Protocol incorporates scientific knowledge on the developmental capabilities of children (e.g., memory functioning, disclosure of abuse) and creates conditions for maximizing children's productivity and the likelihood of accurate statements regarding experiences of abuse (Ahern et al 2015;La Rooy et al 2015).…”
Section: Child Investigative Interviewingmentioning
confidence: 99%
“…This general TPL effect can be observed in the context of RES when the initial interview (or initial test) does not include questions that directly target details that will be contradicted by misinformation later. A prediction borne out by studies that demonstrated RES while employing free recall (Wilford, Chan, & Tuhn, 2014), the Cognitive Interview (LaPaglia, Wilford, Rivard, Chan, & Fisher, 2014), and the NICHD interview protocol as the initial test (Otgaar, Chan, Calado, & La Rooy, 2019). In contrast, a specific TPL effect occurs when a piece of misinformation directly contradicts (or supplements) a previously queried detail.…”
Section: Discussionmentioning
confidence: 99%